PENGARUH TINGKAT PENDIDIKAN, PELATIHAN DAN PENGALAMAN MENGAJAR TERHADAP PROFESIONALISME GURU DI SEKOLAH DASAR NEGERI WILAYAH BINAAN VI JATINEGARA JAKARTA TIMUR - Leonardo Indra Vitaharsa (LPPM Universitas Asa Indonesia, 2018)
Purpose- This study aims to determine the effect of the level of education, training and teaching experience on the professionalism of teachers both partially and together with teachers in Binaan VI Elementary School Jatinegara, East Jakarta Design/methology/approach- The author takes the number of samples according to time constraints and the funds are determined purposively by 75 teachers as respondents. The author uses the method used in this research is descriptive and quantitative with multiple regression analysis techniques. From the results of the study showed there are influences of Education (X1), Training (X2) and Teaching Experience (X3) on Teacher Professionalism (Y) Findings- Significant simultaneously or partially and this is evident from the results of the analysis using the ANOVA model where F counts 33.960 and Ftable with df 2; 72 is 3.15 thus Fcount 33.960> Fcount 33.960 and Ftable then (Ho) is rejected and (Ha) is accepted meaning Education (X1), Training (X2) and Teaching Experience (X3) together have the influence of SDN Teacher Professionalism in the target area VI (Y). The probability of the result is 0,000 at a value of α = 0.05, so the probability is far below the Alpha value so that Education (X1), Training (X2) and Teaching Experience (X3) together have a significant effect on the Professionalism of SDN Teachers in the Foster VI area Cipinang Besar Selatan Jatinegara, East Jakarta. Research limitations- The contribution of the independent variable to the Professionalism of Teacher in SD Binaan VI Elementary School Jatinegara, East Jakarta is 58.9%, while the remaining 41.1% is influenced by other variables not included in the model or not examined.",